The potential of Bursa city parks to provide natural food for urban wildlife - Uğurlu, Zeynep; Yılmaz, Mustafa (My University, 2024)
This study aims to determine the periods during which fruit-bearing woody plant species in the study area parks have ripe fruits, thereby revealing the potential of these parks to provide food resources for urban wildlife. The study was conducted in three major parks in Bursa: Reşat Oyal Culture Park, Soğanlı Botanical Park and Hüdavendigar City Park. To determine the periods and durations during which each plant species bears ripe fruits, the study area parks were visited once a week for one year. During the visits, the times when the fruit-bearing woody plant species had ripe fruits were recorded on a species-time table. Reşat Oyal Culture Park hosts 32 species of fruit-bearing woody plants, Soğanlı Botanical Park has 35 species, and Hüdavendigar City Park hosts 17 species. The oldest park, Reşat Oyal Culture Park, has the highest number of native fruit-bearing plant species with 18, while the newest park, Hüdavendigar Urban Park, has the lowest number with 8 species. On a weekly average, 7.9 plants in Reşat Oyal Culture Park, 9.6 plants in Soğanlı Botanical Park, and 4.8 plants in Hüdavendigar City Park bear ripe fruits. A statistically significant difference was found between the data from Reşat Oyal Culture Park and Soğanlı Botanical Park compared to the data from Hüdavendigar City Park (P>0.05). In urban ecosystems, fruity woody plants provide natural food for urban wildlife. The use of native and fruit-bearing woody plant species in urban plantings has an important role in the sustainability of urban wildlife.